2021
DOI: 10.1002/ehf2.13269
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 induced cardiac hypertrophy through EP2 receptor‐dependent activation of β‐catenin in 5/6 nephrectomy rats

Abstract: Aims Prostaglandin E 2 (PGE2) is involved in the development of cardiac hypertrophy. However, whether PGE2 regulates the chronic kidney disease-associated cardiac hypertrophy and the tentative mechanism remains to be elucidated. Methods and resultsWe explored the effect of PGE2 receptor inhibitors on cardiac hypertrophy in vitro and in a 5/6 nephrectomy (5/6NT) rat model using quantitative reverse transcription polymerase chain reaction, western blotting, enzyme-linked immunosorbent assay, immunohistochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…The binding of EP1 receptors to cardiac fibroblasts seems to increase their proliferation and collagen deposition, worsening cardiac recovery after ischemia [ 203 ]. Instead, EP2 receptors appear to induce cardiac hypertrophy after the interaction with PGE2 in cardiomyocytes [ 204 ].…”
Section: Prostanoidsmentioning
confidence: 99%
“…The binding of EP1 receptors to cardiac fibroblasts seems to increase their proliferation and collagen deposition, worsening cardiac recovery after ischemia [ 203 ]. Instead, EP2 receptors appear to induce cardiac hypertrophy after the interaction with PGE2 in cardiomyocytes [ 204 ].…”
Section: Prostanoidsmentioning
confidence: 99%
“…PGE 2 increases expression of both EP2 and EP4 receptors. EP2 receptor activation enhances expression of TGF-β1, collagen I and III in H9C2 cardiac myocytes [ 21 ]. PGE 2 is the direct enzymatic product of COX-2.…”
Section: Resultsmentioning
confidence: 99%
“…In contrary to inhibition of lung fibroblast proliferation, PGE 2 stimulates cardiac fibroblast proliferation and p42/44 MAPK pathway [ 32 ]. PGE 2 up-regulates expression of EP2 and EP4 as well as levels of fibrosis-associated protein expression such as TGF-β1, collagen I and III in H9C2 cardiac myocytes [ 21 ]. Selective antagonism of EP2 receptor with AH6809 blocks increased expression of TGF-β1, collagen I and III in both cardiac myocytes and a chronic kidney disease-associated cardiac hypertrophy and fibrosis [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In other cases, PGE2-EP2/EP4 signaling mediates the expression of anti-inflammatory cytokines through anti-inflammatory cytokine IL-10 signaling and function [41] . The inhibition of cytokine TGF-β-induced cell proliferation in vivo is directly inhibited by PGE2 through EP2 and EP4 [42] , which might be involved in the PKC–Raf1–MEK1/2–ERK1/2, PKA/AKT, and MAPK/ERK signaling pathways in the prevention of the progression of CKD [43] . In our present study, the normalized NGS gene expression data successfully identified a significant PTGER2 gene, the EP2 protein, that is activated in response to human kidney cells after treatment with an ECE inhibitor by using IPA database analysis.…”
Section: Discussionmentioning
confidence: 99%